DEVELOPING MATHEMATIC LEARNING MEDIA USING MACROMEDIA FLASH 8 FOR FIFTH GRADERS OLEH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This research confers an analysis of (1) the development of interactive media for mathematic learning in elementary schools and (2) the effectiveness of the interactive learning media developed using Macromedia Flash 8. The research method was research and development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model development stage. The data collection technique was validation questionnaires to be responded to by material and media design experts and students’ responses. The media developed was tested on 12 fifth graders at SDN 3 Suwawa Tengah. These interactive media developed using Macromedia Flash 8 for fifth graders were scored 95% by the material expert and as such, were categorized as ‘very reliable’ and 96.25% by the media design expert, and hence, were also categorized as ‘very reliable’. According to students’ responses, the media were scored 96.2% and that being so, were considered ‘very reliable’ as well. After using the interactive learning media developed, students came with a mean score of learning outcome of 85%.